(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2019)
The voice of conscience, in Heideggerian existentialism, stands for humanity’s inherent potency to call himself into an authentic way of living. Heidegger, through this concept, calls us to acknowledge the range of our possibilities in life before death than regret what we have already done. Since authentic living is a process than an end – no salvation being possible in this world – being sensitive to the call is trying to be authentic throughout life. As such, the call acts like taking placebos which keep us hopeful while we are in bad health, although there might be no cure. Paul Auster’s Mr Vertigo, being a novel filled with existential themes, can be read to concretise the existential intonation of Heideggerian conscience, following Auster’s own existential outlook into the human condition. This paper, by applying an interdisciplinary approach, thus reads Mr Vertigo in the light of Heidegger’s certain existential concepts and the implications they have concerning how our existential conscience has a placebo effect. As such, this paper is to argue that Auster’s Yehudi in Mr Vertigo plays the role of Walt’s voice of conscience to help him with an authentic life style, the novel meanwhile highlighting how the call of conscience can help Heidegger’s “Dasein” with the infinity of possibilities it has before death in a world determined by contingency.